Effects of rotigotine transdermal patch in patients with Parkinson's disease presenting with non‐motor symptoms – results of a double‐blind, randomized, placebo‐controlled trial. (22nd June 2015) - Antonini, A.; Bauer, L.; Dohin, E.; Oertel, W. H.; Rascol, O.; Reichmann, H.; Schmid, M.; Singh, P.; Tolosa, E.; Chaudhuri, K. Ray
Abstract : Background and purpose: Non‐motor symptoms (NMS) of Parkinson's disease (PD) have a major impact on health‐related quality of life. This is the first randomized controlled trial to use the NMS Scale (NMSS) as a primary outcome to assess treatment effects on NMS in PD. Methods: In this double‐blind trial (NCT01300819), patients with PD and a total NMSS score ≥40 were randomized (2:1) to rotigotine or placebo, titrated over 1–7 weeks to optimal dose (≤8 mg/24 h for patients not receiving levodopa, ≤16 mg/24 h for patients receiving levodopa), maintained for 12 weeks. The primary outcome was change in NMSS total score from baseline to end of maintenance. Secondary outcomes were the nine NMSS domains, Unified Parkinson's Disease Rating Scale (UPDRS) III (motor) and the 39‐item Parkinson's Disease Questionnaire (PDQ‐39). Results: In total, 283/349 (81.1%) randomized patients completed the trial; 211 rotigotine and 122 placebo were included in the full analysis set. The NMSS total score decreased by 23 (rotigotine) and 19 (placebo) points; the treatment difference was not statistically significant (−3.58; 95% confidence interval −8.43, 1.26; P  =   0.147). Numerically greater than placebo improvements were detected in the 'mood/apathy' and 'miscellaneous' NMSS domains ( P  <   0.05). Treatment differences in UPDRS III (−2.60; −4.27, −0.92; P  =   0.002) and PDQ‐39 (−2.79; −5.21, −0.37; P  =   0.024) favoured rotigotine. Adverse events reported more frequently with rotigotine were nausea, application site reactions, somnolence and headache. Conclusions: Rotigotine improvement in the multi‐domain NMSS total score was not superior to placebo. A different sensitivity of individual NMSS domains to dopaminergic therapy and a large placebo effect may have contributed to these findings.